Infiltrating myoepithelial carcinoma of the breast, a case report and cytologic-histologic correlation - Kure Kiyoe; Chen Yayan; Lingamfelter Daniel; Lankachandra Kamani (BMC, 2008)
Abstract Introduction Infiltrating myoepithelial carcinoma remains a rarely encountered lesion of the breast. The few cases that have surfaced firmly document the histopathology of this tumor, but its cytologic characteristics seemingly have been described in only one other report. Case presentation Here we present the cytologic findings from a case of infiltrating myoepithelial carcinoma of the breast in a 52-year-old female and provide a histologic correlation with the subsequent biopsy and mastectomy specimens. While the cytology specimens displayed more myoepithelial cellular heterogeneity than was present on histology, a number of cytologic features including hypercellularity, pleomorphic spindle cells, and mitotic activity correlated well with the histopathology. Conclusion The role of fine needle aspiration in the diagnosis of mammary myoepithelial carcinoma, in this case, was to establish malignancy rather than to arrive at a specific diagnosis, as a number of different entities potentially can mimic this neoplasm on cytologic specimens.